Pengaruh Family Edukasi Dengan Media Leaflet Persuasif Tentang Pencegahan Covid-19 Terhadap Pengetahuan Dan Sikap Masyarakat Sekitar Penderita Covid-19 - Munjiati Munjiati; Welas Haryati; Ratifah Ratifah (JURNAL KEPERAWATAN MERSI, 2021)
Background: COVID-19 (Coronavirus Disease-19) is one of the respiratory tract infections that can cause death with a very high transmission rate. Objective: To identify the effect of using persuasive leaflet media on the prevention of COVID-19 on the knowledge and attitudes of people living around COVID-19 sufferers. Methods: The method used is a  quasi- experimental study by providing treatment using persuasive leaflets about preventing COVID-19 in family education activities. The measurements used were pre- and post-test with control group design, where the measurements differed between before and after treatment. The difference between before and after the intervention is assumed to be the effect of the intervention. The population in this study is the community around COVID-19 sufferers. Furthermore, the sampling technique used was purposive sampling with inclusion criteria, namely the community around people with COVID-19, minimum education in elementary school, able to read and write, came from the area around Kober.The results: of this study indicate that the mean difference in pre and post knowledge scores in the treatment group is 1.23 while in the control group is 0.03. Meanwhile, the mean difference between pre and post attitude scores in the treatment group was 0.93 while in the control group it was 0.07. This shows that there are significant differences in attitudes and attitudes in the treatment group after being treated with educational leaflets.Conclusion: The p-value at the knowledge level is 0.00 and for the attitude level is 0.01. This shows that there is a significant effect of family education persuasive leaflet media in preventing COVID-19 disease on the level of knowledge and attitudes of families around the community with COVID-19 for the treatment group while in the control group it is not